Contemporary management - George, Jennifer M. (New York, NY McGraw Hill, 2024)
"In this 2024 Release of Contemporary Management, we continue to focus on providing the most up-to-date account of the changes taking place in the world of management and management practices while maintaining our emphasis on keeping our text relevant and interesting to students. Our increased focus on the challenges and opportunities facing businesses large and small and integrated timely examples bring management issues to life for students"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Management